Arthroscopic Technique of Capsular Plication for the Treatment of Hip Instability - Chandrasekaran, Sivashankar (Arthrosc Tech, 2015)
Atraumatic instability or microinstability of the hip is a recognized cause of groin pain and hip instability. Risk factors include female sex, ligamentous laxity, and borderline dysplasia. Arthroscopically, the joint may distract easily, and there may be associated ligamentum teres tears and laxity of the capsule on manual probing. The use of arthroscopic capsular plication in this cohort of patients has shown good to excellent results. Biomechanically, a capsular plication aims to create an imbrication and inferior shift of the capsule to augment the screw-home mechanism of the capsuloligamentous structures and thereby improve stability in extension and external rotation. The purpose of this article is to detail the step-by-step surgical technique of arthroscopic capsular plication, in addition to the indications, pearls, and pitfalls of the technique.